2008
DOI: 10.1103/physrevb.78.115428
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of periodically meandered one-dimensional Fe nanowires

Abstract: We study the magnetic structure of perpendicularly magnetized Fe nanowires grown on Au͑788͒ by means of x-ray magnetic circular dichroism. The average size of ferromagnetic domains in the nanowires exponentially decreases with temperature, leading to a steeper decay in magnetization compared to nanoislands of Fe. The temperature dependence of magnetization and domain structures can be well described in terms of local atomic geometry, the number of atomic chains in nanowires, exchange coupling between adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Gambardella et al 6 observed both long- and short-range magnetic order in Co chains arranged on a Pt(997) surface, with a blocking temperature of 15 K for the long-range order. In meandered Fe nanowires grown on Au(788), Shiraki et al 9 confirmed the theoretical expectation1011 that the average size of the ferromagnetic domains in the nanowire decreases exponentially with temperature. Strigl et al 1 showed experimentally that even nanowires of platinum, which is paramagnetic in bulk, demonstrate signatures of local magnetic order.…”
mentioning
confidence: 71%
“…Gambardella et al 6 observed both long- and short-range magnetic order in Co chains arranged on a Pt(997) surface, with a blocking temperature of 15 K for the long-range order. In meandered Fe nanowires grown on Au(788), Shiraki et al 9 confirmed the theoretical expectation1011 that the average size of the ferromagnetic domains in the nanowire decreases exponentially with temperature. Strigl et al 1 showed experimentally that even nanowires of platinum, which is paramagnetic in bulk, demonstrate signatures of local magnetic order.…”
mentioning
confidence: 71%
“…31,32 The influence of size and shape of nanowire on magnetic domain pattern in 1D Fe nanowire has also been revealed very recently. 33 In our previous work, the role of Pt spacer in tuning the FM property of Fe/Pt nanowire is addressed. 34 The average magnetic moment per Fe atom is found to increase with the increase in Pt spacer width and has been shown to follow an ϳ1 / N Fe trend; N Fe is the number of Fe layers in the Fe/Pt nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of the surface science drifts nowadays towards atomic‐scale systems, e.g., wires 1–11, stripes 2, 12–18, clusters 1, 19–25, and nanodots 26–32. Such downscaling requires realistic and efficient ways of description of systems, whose properties are determined by quantum effects and, therefore, are strongly dependent on the environment, dimension, structure, and atomic species involved 33.…”
Section: Introductionmentioning
confidence: 99%
“…The next interesting aspect of our study is related to creation of low‐dimensional nanostructures on surfaces 33. They could be self‐assembled in a “bottom‐up” manner 1–30, 33–40, or built in a “top‐down” approach by means of the scanning tunneling microscopy (STM) 41–49. The latter technique allows to map surface topography at the atomic scale 50–53 or even with a true atomic resolution 54 and to record simultaneously spectral characteristics of the sample studied 55–57.…”
Section: Introductionmentioning
confidence: 99%